Induction of Apoptosis by Luteolin Involving Akt Inactivation in Human 786-O Renal Cell Carcinoma Cells. (5th February 2013) - Ou, Yen-Chuan; Kuan, Yu-Hsiang; Li, Jian-Ri; Raung, Shue-Ling; Wang, Chung-Chiang; Hung, Yu-Yeh; Chen, Chun-Jung
Abstract : There is a growing interest in the health-promoting effects of natural substances obtained from plants. Although luteolin has been identified as a potential therapeutic and preventive agent for cancer because of its potent cancer cell-killing activity, the molecular mechanisms have not been well elucidated. This study provides evidence of an alternative target for luteolin and sheds light on the mechanism of its physiological benefits. Treatment of 786-O renal cell carcinoma (RCC) cells (as well as A498 and ACHN) with luteolin caused cell apoptosis and death. This cytotoxicity was caused by the downregulation of Akt and resultant upregulation of apoptosis signal-regulating kinase-1 (Ask1), p38, and c-Jun N-terminal kinase (JNK) activities, probably via protein phosphatase 2A (PP2A) activation. In addition to being a concurrent substrate of caspases and event of cell death, heat shock protein-90 (HSP90) cleavage might also play a role in driving further cellular alterations and cell death, at least in part, involving an Akt-related mechanism. Due to the high expression of HSP90 and Akt-related molecules in RCC and other cancer cells, our findings suggest that PP2A activation might work in concert with HSP90 cleavage to inactivate Akt and lead to a vicious caspase-dependent apoptotic cycle in luteolin-treated 786-O cells.